Rail transport between China and Europe on the New Silk Road in times of crisis - Mirosław Antonowicz (Przegląd Komunikacyjny)
Abstract: The aim of this article is to synthetically assess the impact of crisis phenomena on transport volumes in rail cargo transport between Asia and Europe on the rail Silk Road. The analysis of secondary sources and the analysis of transport results in traffic between China and Europe was carried out on the basis of data and statistical quantities obtained as part of analytical and research work in the field of freight traffic within the framework of the Organization for Co-Operation between Railways (OSJD). The analysis confirmed that freight traffic between China and Europe has shown its stability in transport volumes. The actions taken by the railways of the member states of the OSJD to counteract the crisis phenomena resulted in the achievement of positive transport results and an increase in container transport in international rail traffic between Asia and Europe on the rail Silk Road. The results of the analyses showed an increase in container transport in the China-Europe-China relations in the rail transport corridors operating under the New Silk Road concept. Nevertheless, the crisis has highlighted changes in transport on the Northern Corridor and efforts to search for alternative transport corridors. The main indicators of international rail transport in transit transport between Asia and Europe turned out to be the speed of transport and the time of delivery of goods. The transport results were influenced by work on the development and organization of container transport in international traffic, including the organization of container block trains, digitization of service processes at border crossings, and the CIM/SMGS consignment note.